Toward a Dimensional Assessment of Externalizing Disorders in Children: Reliability and Validity of a Semi-Structured Parent Interview - Thöne, Ann-Kathrin; Görtz-Dorten, Anja; Altenberger, Paula; Dose, Christina; Geldermann, Nina; Hautmann, Christopher; Jendreizik, Lea Teresa; Treier, Anne-Katrin; von Wirth, Elena; Banaschewski, Tobias; Brandeis, Daniel; Millenet, Sabina; et al. (Frontiers in Psychology, 2020)
Objective: This study assesses the reliability and validity of the DSM-5-based, semi-structured Clinical Parent Interview for Externalizing Disorders in Children and Adolescents (ILF-EXTERNAL). Method: Participant data were drawn from the ongoing ESCAschool intervention study. The ILF-EXTERNAL was evaluated in a clinical sample of 474 children and adolescents (aged 6 - 12 years, 92 females) with symptoms of attention-deficit/hyperactivity disorder (ADHD). To obtain interrater reliability, the one-way random-effects, absolute agreement models of the intraclass correlation (ICC) for single ICC(1,1) and average measurements ICC(1,3) were computed between the interviewers and two independent raters for 45 randomly selected interviews involving ten interviewers. Overall agreement on DSM-5 diagnoses was assessed using Fleiss’ kappa. Further analyses evaluated internal consistencies, item-total correlations as well as correlations between symptom severity and the degree of functional impairment. Additionally, parents completed the German version of the Child Behavior Checklist (CBCL) and two DSM-5-based parent questionnaires for the assessment of ADHD symptoms and symptoms of disruptive behavior disorders (FBB-ADHS; FBB-SSV), which were used to evaluate convergent and divergent validity. Results: ICC coefficients demonstrated very good to excellent interrater reliability on the item and scale level of the ILF-EXTERNAL (scale level: ICC(1,1) = .83 - .95; ICC(1,3) = .94 - .98). Overall kappa agreement on DSM-5 diagnoses was substantial to almost perfect for most disorders. With some exceptions, internal consistencies (.60 ≤ α. ≤ 86) and item-total correlations (.21 ≤ rit ≤ 71) were generally satisfactory to good. Furthermore, higher symptom severity was associated with a higher degree of functional impairment. The evaluation of convergent validity revealed positive results regarding clinical judgment and parent ratings (FBB-ADHS; FBB-SSV). Correlations between the ILF-EXTERNAL scales and the CBCL Externalizing Problems were moderate to high. Finally, the ILF-EXTERNAL scales were significantly more strongly associated with the CBCL Externalizing Problems than with the Internalizing Problems, indicating divergent validity. Conclusion: In clinically referred, school-age children, the ILF-EXTERNAL demonstrates sound psychometric properties. The ILF-EXTERNAL is a promising clinical interview and contributes to high-quality diagnostics of externalizing disorders in children and adolescents.